Rare TACI Mutation in a 3-Year-Old Boy With CVID Phenotype - Leonardi, Lucia; Lorenzetti, Giulia; Carsetti, Rita; Ferrari, Simona; Di Felice, Alessia; Cinicola, Bianca; Duse, Marzia (Frontiers in Pediatrics, 2019)
Common variable immunodeficiency (CVID) is the most common and clinically relevant primary immunodeficiency (PID). Genetic basis of CVID remains largely unknown. However, in a minority of CVID patients, a number of distinct genetic defects affecting the normal processes of B cell maturation and differentiation into memory B cells have now been identified, resulting in markedly reduced serum levels of immunoglobulin G (IgG) and low immunoglobulin A (IgA) or immunoglobulin M (IgM), with impaired antibody responses, despite the presence of normal levels of B cells. Patients with CVID develop recurrent and chronic infections of respiratory and gastrointestinal tracts, autoimmune diseases, lymphoproliferative complications, malignancies and granulomatous disease. We report the case of a boy admitted to our unit for the first time at the age of three for reduced gamma globulin levels and a clinical history positive for two episodes of pneumonia. Our patient incompletely met the Revised ESID (2014) diagnostic criteria for CVID, but molecular genetic analysis, a NGS panel including 47 PID-associated genes was performed in the proband and in his parents, revealing the presence of a heterozygous nucleotide substitution in exon 4 (c.579C>A) of TNFRSF13B encoding TACI. This mutation has been described only in two CVID adult patients and in a child with selective IgA deficiency (sIgAD). We highlighted the same mutation in the asymptomatic mother and detected two extra heterozygous mutations of RIG1 and LIG1. We promptly started intravenous immunoglobulin (IVIG) therapy with good tolerance. Despite the diagnosis of CVID remains clinical, in this case report we underline the importance of considering and planning genetic workup in all subjects with unclear diagnosis and of reporting new molecular diagnosis especially in case of rare mutations.